Interaction of rice residue and PRE herbicides on emergence and biomass of four weed species - Chauhan, Bhagirath S.; Abugho, Seth B. (Cambridge University Press, 2012)
Studies were conducted in a screenhouse to determine the interaction of rice residue as mulch (0, 3, and 6 t ha−1) and herbicides (nontreated, oxadiazon at 0.5 and 1.0 kg ai ha−1, and pendimethalin at 1.0 and 2.0 kg ai ha−1) on seedling emergence and biomass of barnyardgrass, crowfootgrass, junglerice, and rice flatsedge. Regardless of the residue amount, crowfootgrass and junglerice were effectively controlled by all herbicide treatments. No seedlings of these weed species escaped the herbicides when applied in the presence of residue cover. There was no survival of barnyardgrass seedlings when both herbicides were applied on bare soil (without residue cover); however, some seedlings survived oxadiazon and pendimethalin when applied in the presence of residue cover. For rice flatsedge, the herbicide applications in the presence of residue cover resulted in lower weed control than in the absence of residue. These results suggest that some weed species can escape the application of PRE herbicides in conservation agriculture systems in which residue can bind soil-applied herbicides and result in lower efficacy.